The impact of small food workshops management regulations on aflatoxin B1 in home-made peanut oil and the liver function of high-consumption area residents: an interrupted time series study in Guangzhou, China - Lei, Jiangbo; Li, Yan; Wang, Yanyan; Zhou, Jinchang; Wu, Yuzhe; Zhang, Yuhua; Liu, Lan; Ou, Yijun; Huang, Lili; Wu, Sixuan; Guo, Xuanya; Liu, Lieyan; et al. (Frontiers in Public Health, 2024)
BackgroundAflatoxin B1 (AFB1), a potent carcinogen produced by Aspergillus species, is a prevalent contaminant in oil crops, with prolonged exposure associated with liver damage. Home-made peanut oil (HMPO) produced by small workshops in Guangzhou is heavily contaminated with AFB1. Despite the enactment of the Small Food Workshops Management Regulations (SFWMR), no quantitative assessment has been conducted regarding its impact on food contamination and public health. The study aims to assess the impact of SFWMR on AFB1 contamination in HMPO and liver function in the population.MethodAFB1 contamination in HMPO were quantified using high-performance liquid chromatography and liver function data were obtained from the health center located in a high-HMPO-consumption area in Guangzhou. Interrupted time series and mediation analyses were employed to assess the relationship between the implementation of SFWMR, AFB1 concentrations in HMPO, and liver function among residents.ResultThe AFB1 concentrations in HMPO were 1.29 (0.12, 6.58) μg/kg. The average daily intake of AFB1 through HMPO for Guangzhou residents from 2010 to 2022 ranged from 0.25 to 1.68 ng/kg bw/d, and the Margin of Exposure ranged from 238 to 1,600. The implementation of SFWMR was associated with a significant reduction in AFB1 concentrations in HMPO, showing an immediate decrease of 2.865 μg/kg (P = 0.006) and a sustained annual reduction of 2.593 μg/kg (P = 0.034). Among residents in the high-HMPO-consumption area, the implementation of SFWMR was significantly associated with a reduction in the prevalence of liver function abnormality (PR = 0.650, 95% CI: 0.469–0.902). Subgroup analysis revealed that this reduction was significantly associated with the implementation of SFWMR in the female (PR = 0.484, 95% CI: 0.310–0.755) and in individuals aged ≥ 60 years (PR = 0.586, 95% CI: 0.395–0.868). Mediation analysis demonstrated that AFB1 concentrations in HMPO fully mediated the relationship between the implementation of SFWMR and the liver function abnormality (PR = 0.981, 95% CI: 0.969–0.993).ConclusionIn Guangzhou, the public health issue arising from AFB1 intake through HMPO warrants attention. The implementation of SFWMR had a positive impact on the improvement of AFB1 contamination in HMPO and the liver function. Continued efforts are necessary to strengthen the enforcement of the regulations. The exposure risks to AFB1 among high-HMPO-consumption groups also demand greater focus.